The Refugee Issue In The Supreme Council Of The Republic OfArmenia In The Context Of State Building In 1990-1991 - Zakaryan, Lilit (ՀՀ ԳԱԱ)
In July 1990, the newly elected Supreme Council of the Armenian SSR began state building by adopting the Declaration of Independence. In the context of the enormous problems of state-building, the Karabakh issue was sometimes relegated to the background. However, the intensification of the policy of persecution of Armenians in Azerbaijan, new manifestations of the mass deportation of Armenians with the consent and participation of the power structures of the agonizing Soviet empire forced the Supreme Council to bring it back to the agenda. The article deals with the discussion of the issues of mass deportation of Armenians in the Supreme Council of the Republic of Armenia and the forced change of the policy vector in the context of state-building.
Keywords: Refugees